1992
DOI: 10.1091/mbc.3.3.335
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane-mediated changes in [Ca2+] are involved in the signaling pathway leading to macrophage cytocidal differentiation: implications of localized changes in intracellular [Ca2+] and of interferon priming on Ca2+ utilization.

Abstract: Macrophage cytocidal activation requires the sequential impingement on the macrophage of a priming stimulus (interferon [IFN]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 70 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…1, 2A, 3, 6, 7). Although these millimolar concentrations are generally at least an order of magnitude greater than the levels found to be effective with animal cells (Underwood and Riches, 1992), lower plants (Conrad and Hepler, 1988;Kataoka, 1990;Wacker and Schnepf, 1990), plant cell cultures (Roberts and Haigler, 1990), or protoplasts (Graziana et al, 1988), they are comparable to the concentrations that inhibit the growth of pea stem sections (Cunninghame and Hall, 1986;Brummell and Machlachlan, 1989) and maize roots (Perdue et al, 1988). None of the antagonists, except lanthanum at a very high concentration of 100 mM, was found to inhibit the relatively small amount of growth in nonhormone-treated segments.…”
Section: Dlscusslonmentioning
confidence: 85%
“…1, 2A, 3, 6, 7). Although these millimolar concentrations are generally at least an order of magnitude greater than the levels found to be effective with animal cells (Underwood and Riches, 1992), lower plants (Conrad and Hepler, 1988;Kataoka, 1990;Wacker and Schnepf, 1990), plant cell cultures (Roberts and Haigler, 1990), or protoplasts (Graziana et al, 1988), they are comparable to the concentrations that inhibit the growth of pea stem sections (Cunninghame and Hall, 1986;Brummell and Machlachlan, 1989) and maize roots (Perdue et al, 1988). None of the antagonists, except lanthanum at a very high concentration of 100 mM, was found to inhibit the relatively small amount of growth in nonhormone-treated segments.…”
Section: Dlscusslonmentioning
confidence: 85%
“…We chose to study monocytes because of their central role in the endometrio sis-associated inflammatory process [1][2][3], Furthermore, the ability of verapamil to abrogate specific calciumdependent macrophage functions was extensively docu mented. It has been demonstrated that the drug is able to inhibit a variety of monocyte-adhesive properties coordi nated by the CD llb/C D 18 complex by blocking the phase of ADP-induced calcium entry [13]; calcium chan nel blockers can impair the calcium-dependent cytotoxic activity of macrophage cytotoxins [14]; the macrophage differentiation from the interferon-primed state to the cytocidal state is substantially inhibited by verapamil [ 12].…”
Section: Discussionmentioning
confidence: 99%
“…Danazol, for instance, has an in vitro inhibitory effect on conventional macrophage-de pendent T lymphocyte mitogenic response to phyto hemagglutinin, concanavalin A and allogeneic mixed lymphocyte culture [8], Furthermore, the drug has been shown to inhibit the production of interleukin-1(3 and tumor necrosis factor by monocytes stimulated by OK-432 (a streptococcal preparation) in a dose-dependent manner [9], Gestrinone significantly suppresses macro phage phagocytosis at a pharmacological concentration and concanavalin-A-induced lymphocyte blastogenesis at a slightly higher concentration than that attained in wom en taking 2 x 2.5 mg weekly [10], Steinleitner et al [11] have recently proposed vera pamil, a calcium-channel-blocking agent, as an alternative approach to the medical or surgical standard management for the treatment of endometriosis-associated intraperito neal inflammatory cell activation. It is well known that verapamil is able to exert some adverse influence on leu kocyte function [12][13][14]; moreover, drugs with calciumchannel-blocking properties do not affect ovulation and do not seem to have any teratogenic effects [15,16], In view of these new aspects related to the medical treatment of endometriosis-associated infertility, the present study was designed to compare the immunosup pressive effects of danazol, gestrinone and verapamil on human monocyte phagocytosis in order to assess any sig nificant differences in their ability to influence a parame ter of inflammatory cell function.…”
Section: Introductionmentioning
confidence: 99%
“…Using these mechanisms to induce a number of genes, IFN‐γ plays an important role in host defense and inflammation. IFN‐γ activates macrophages, which results in the induction of a number of different cytokines and the induction of anti‐infective properties resulting in enhanced microbicidal activity 24.…”
Section: Introductionmentioning
confidence: 99%